PENGUJIAN FAMA-FRENCH THREE-FACTOR MODEL DI INDONESIA - Damar Hardianto; Suherman Suherman (Jurnal Keuangan dan Perbankan, 2009)
This study empirically examined the Fama-French three factor model of stock returnsfor Indonesia over the period 2000-2004. We found evidence for pervasive market, size, andbook-to-market factors in Indonesian stock returns. We found that cross-sectional mean returnswere explained by exposures to these three factors, and not by the market factor alone. Theempirical results were reasonably consistent with the Fama-French three factor model.